Molecular analyses of nonribosomal peptide synthetase in Ganoderma boninense - Chua, Jackie (2015)
Oil palm plays a significant role in Malaysia’s economy as Malaysia is the secondlargest palm oil producer after Indonesia. However, the basal stem rot disease (BSR) caused by G. boninense, a basidiomycete fungus has affected oil palm yields in most production areas. Many methods to control the disease have been developed but to date, there is no control of BSR disease in the field. Fungi were reported to produce variety of secondary metabolites. Some secondary metabolites are toxic to host plant and may act as virulence factors. Secondary metabolite especially produced by nonribosomal peptide synthetase (NRPS) has recently gained interest due to its wide array of biological activities and virulence factors. Hence, the understanding of fungal secondary metabolism of NRPS at molecular level is essential. In this work, detection of NRPS in G. boninense was achieved using PCR-based and biochemical methods. Primers targeted to NRPS conserved region of adenylation (A) domain were used to molecular characterize NRPS. To correlate NRPS and disease incidence during Ganoderma-oil palm interaction, RT-PCR was done conducted using samples obtained from glasshouse trial. Chrome Azurol S (CAS) agar plate assay with incorporation of CAS-blue dye was used for siderophore detection. PCR products were sequenced, translated and nucleotide sequences were searched against NCBI database using BLAST tool. The PCR fragments showed similarity to the conserved region of adenylation domain: A2 (LKAGxAYL(VL)P(LI)D, A3 (TSG(TS)TGxPKxV) and A5 (NxYGPxE). A-domain is important as it is the core element of NRPS modules. A-domain acts as the selector and the activator of the cognate substrate. Colour-change reaction in the CAS-blue agar showed the production of siderophore by G. boninense. The colour change occurred as a result of ferric iron transfer from the reagent complex to siderophore present in the fungus. In other reports, NRPS genes are found to be involved in the biosynthesis of siderophores, toxins involved in pathogenesis. RT-PCR of the oil palm samples showed the same fragment size of NRPS as detected in Ganoderma fungus. Both progenies of susceptible and tolerant oil palm seedlings showed visible disease symptoms at 4 months after infection. However, RT-PCR of NRPS expressed as early as 1 month after infection and consistent expression at 4 months after infection onwards for both susceptible and tolerant progeny. Information related to NRPS of G. boninense obtained in this study will facilitate the understanding of the potential evolution of Ganoderma NRPS. Further studies and analysis of these genes and their peptide products may identify important roles of secondary metabolites produced by NRPS in Ganoderma physiology, ecology or fungal pathogenicity. This study is the first evidence for the present of NRPS in the genome of G. boninense and also its involvement in BSR disease of oil palm.